The Desert and the Pastoralist: An Archaeological Perspective on Human-Landscape Interaction in the Negev over the Millennia - Rosen, Steven A (Annals of Arid Zone, 2016)
Analysis of patterns of settlement over the long term in the Negev, the desert of southern Israel, reflects repeated cycles of demographic decline and florescence, ostensibly cycles of desertification and re-colonization or growth. Although these periods of decline can be associated with parallel declines in production, and sometimes landscape degradation, these episodes of desertification cannot be tied to pastoral over-exploitation. The linkage between overgrazing and desertification in the Negev appears to be exclusively a modern one, and extrapolation of modern processes and conditions into the deep past is unwarranted. Key words: Negev, pastoralism, overgrazing, nomadism, desertification